2017
DOI: 10.1016/j.foodchem.2016.07.052
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding for identification of consumer-relevant mushrooms: A partial solution for product certification?

Abstract: One challenge in the dietary supplement industry is confirmation of species identity for processed raw materials, i.e. those modified by milling, drying, or extraction, which move through a multilevel supply chain before reaching the finished product. This is particularly difficult for samples containing fungal mycelia, where processing removes morphological characteristics, such that they do not present sufficient variation to differentiate species by traditional techniques. To address this issue, we have dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 71 publications
2
69
0
Order By: Relevance
“…The ITS region was PCR amplified using primers ITS5 and ITS4 (White et al, 1990), the partial LSU region was amplified using LROR and LR6 (Vilgalys and Hester, 1990), while the tef1 region, specifically intron 4 in combination with intron 5, which is useful for species-level identification, was obtained using primer combinations 983F/728F and 2218R (Carbone and Kohn, 1999; Jaklitsch et al, 2005). Protocols for Sanger sequencing were as outlined previously (Raja et al, 2017a; Raja et al, 2015). All three sequences were subject to a BLAST search in NCBI GenBank to verify their identity.…”
Section: Methodsmentioning
confidence: 99%
“…The ITS region was PCR amplified using primers ITS5 and ITS4 (White et al, 1990), the partial LSU region was amplified using LROR and LR6 (Vilgalys and Hester, 1990), while the tef1 region, specifically intron 4 in combination with intron 5, which is useful for species-level identification, was obtained using primer combinations 983F/728F and 2218R (Carbone and Kohn, 1999; Jaklitsch et al, 2005). Protocols for Sanger sequencing were as outlined previously (Raja et al, 2017a; Raja et al, 2015). All three sequences were subject to a BLAST search in NCBI GenBank to verify their identity.…”
Section: Methodsmentioning
confidence: 99%
“…A spore print should also be prepared in identification process of fleshy mushrooms before can be compared their morphologies with published literature such as [18] and [15] In future, Ganoderma isolate and field-collected basidiomycete isolates will be identified by using molecular approaches for species identification. According to [24], DNA-based molecular markers with particular PCRbased methods were quick and reliable approaches to reveal identities of wild mushrooms. Many studies proven that internal transcribed spacer (ITS) region can be used as a potential DNA barcode marker for fungal phylogenetic analyses and species identification [30], [4], [29], [24], [27].…”
Section: In Vitro Antagonistic Activity For Selected Fungal Species Amentioning
confidence: 99%
“…According to [24], DNA-based molecular markers with particular PCRbased methods were quick and reliable approaches to reveal identities of wild mushrooms. Many studies proven that internal transcribed spacer (ITS) region can be used as a potential DNA barcode marker for fungal phylogenetic analyses and species identification [30], [4], [29], [24], [27]. Meanwhile [35] suggested that the taxonomical classification of mushroom species can be done in combination between their morphological and molecular descriptions which then could give more accurate knowledge and information about their identity and diversity.…”
Section: In Vitro Antagonistic Activity For Selected Fungal Species Amentioning
confidence: 99%
“…Each sequence fragment was subjected to an individual Basic Local Alignment Search Tool (BLAST) (Altschul et al 1990) search in NCBI GenBank to verify its identity. Detailed BLAST search using ITS data were conducted utilizing only published sequences as outlined previously (Raja et al 2017).…”
Section: Phylogenetic Analysismentioning
confidence: 99%